2013
DOI: 10.1007/s00394-013-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

Different postprandial acute response in healthy subjects to three strawberry jams varying in carbohydrate and antioxidant content: a randomized, crossover trial

Abstract: Methods: Sixteen healthy adults participated in a randomized, crossover, double-blind study with three arms, receiving 60g of three different strawberry jams. Blood samples were collected at fasting and at 30, 60, 90 and 120 min after its intake. Blood analyses were performed with validated procedures and satiety was estimated with visual analogue scale (VAS).Results: Blood glucose concentrations were maintained at normal values and without peaks within the 2 h after consumption of low-sugar jams. However, blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
0
7
1
Order By: Relevance
“…This antioxidant effect is probably related with the radical scavenging capacity of cocoa flavanols, which protects cells against oxidative stress and endothelial dysfunction (11). Other hypothesis could be that men were more oxidised than women, thus, the effect of cocoa flavanalos is more effective, given that some studies have not observed additional benefits after intake of antioxidants (29).…”
Section: Discussionmentioning
confidence: 99%
“…This antioxidant effect is probably related with the radical scavenging capacity of cocoa flavanols, which protects cells against oxidative stress and endothelial dysfunction (11). Other hypothesis could be that men were more oxidised than women, thus, the effect of cocoa flavanalos is more effective, given that some studies have not observed additional benefits after intake of antioxidants (29).…”
Section: Discussionmentioning
confidence: 99%
“…Sugar-rich strawberry jam consumption also attenuated glycemic index and postprandial glucose level increases in diabetic human subjects [ 145 , 298 ]. Strawberry jam consumption showed favorable lipid and sugar metabolism results, even compared with low-sugar strawberry jam [ 146 ]. Strawberry consumption with HCD also controlled postprandial glucose levels, affected glucose and insulin responses, and GLP-1 expression.…”
Section: Strawberriesmentioning
confidence: 99%
“…On the contrary, no additional benefits were observed after the addition of natural antioxidants to a lowsugar jam. 97 In addition, freeze-dried strawberry powder effects were detected in females with three features of metabolic syndrome. 98 After short time supplementation, TC and LDLcholesterol levels significantly decreased compared to baseline, but no modification in inflammation markers, such as adiponectin and CPR, were observed.…”
Section: Neuroprotective Activitiesmentioning
confidence: 99%
“…In a crossover, randomized, double-blind study, the effects of an acute intake of strawberry jam on lipid profile, antioxidant status, postprandial glucose metabolism, and satiety were investigated . Compared to jam with added sugar, a more favoring postprandial blood glucose level was obtained with low-sugar jam.…”
Section: Clinical Effects Of Strawberriesmentioning
confidence: 99%